2012
DOI: 10.1088/1741-2560/9/4/045002
|View full text |Cite
|
Sign up to set email alerts
|

Introducing the tactile speller: an ERP-based brain–computer interface for communication

Abstract: In this study, a tactile speller was developed and compared with existing visual speller paradigms in terms of classification performance and elicited event-related potentials (ERPs). The fingertips of healthy participants were stimulated with short mechanical taps while electroencephalographic activity was measured. The letters of the alphabet were allocated to different fingers and subjects could select one of the fingers by silently counting the number of taps on that finger. The offline and online performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 29 publications
6
58
0
Order By: Relevance
“…For example, several gaze-independent BCIs have been reported previously; visual BCIs, auditory BCIs, and tactile BCIs are three main categories (Riccio et al, 2012). A Hex-O speller, which needed covertly directed attention to a target, is a gaze-independent visual BCI (Treder and Blankertz, 2010, Marjolein van der et al, 2012). Severens et al showed that patients with moderate ALS could achieve high performance in a copy-spelling task with the Hex-O speller (Severens et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For example, several gaze-independent BCIs have been reported previously; visual BCIs, auditory BCIs, and tactile BCIs are three main categories (Riccio et al, 2012). A Hex-O speller, which needed covertly directed attention to a target, is a gaze-independent visual BCI (Treder and Blankertz, 2010, Marjolein van der et al, 2012). Severens et al showed that patients with moderate ALS could achieve high performance in a copy-spelling task with the Hex-O speller (Severens et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A recent report [12] proposed using a Braille stimulator with 100 ms static push stimuli delivered to each of six fingers to evoke a somatosensory response potential (SEP) related P300. The P300 response is a positive electroencephalogram event-related potential (ERP) deflection starting at around 300 ms and lasting for 200 − 300 ms after an expected stimulus in a random series of distractors (the so-called oddball EEG experimental paradigm) [7].…”
mentioning
confidence: 99%
“…The P300 responses are commonly used in BCI approaches and are considered to be the most reliable ERPs [16,21] with even beginner subjects. The results in [20] indicated that the experiments achieved information transfer rates of 7.8 bit/min on average and 27 bit/min for the best subject. A very recent report [7] additionally confirmed superiority of the tactile BCI (tBCI) in comparison with visual and auditory modalities tested with a locked-in syndrome (LIS) subject [14].…”
Section: Introductionmentioning
confidence: 92%
“…A more recent report [20] proposed using a Braille stimulator with 100 ms static push stimulus delivered to each of six fingers to evoke a somatosensory evoked potential (SEP) response and the following P300. The P300 response is a positive electroencephalogram event-related potential (ERP) deflection starting at around 300 ms and lasting for 200 − 300 ms after an expected stimulus in a random series of distractors (the so-called oddball EEG experimental paradigm) [13].…”
Section: Introductionmentioning
confidence: 99%